Pengaruh Pendekatan Cognitive Behavioral Therapy Terhadap Masalah Emosi Remaja Di SMP Negeri 1 Kopang - Muhammad Rizaldi; Zaenal Rifky Rabbani (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study aims to examine the effect of the Cognitive Behavioral Therapy (CBT) approach on emotional problems among adolescents at SMP Negeri 1 Kopang. Emotional problems experienced by adolescents at the junior high school level are often related to academic stress, social pressure, and an inability to manage emotions effectively. The CBT approach was chosen because it has been proven effective in helping individuals recognize and change negative thought patterns and maladaptive behaviors. This research employed a quasi-experimental method with a single-group pretest-posttest design. The research sample consisted of 30 students selected through purposive sampling based on initial assessment results indicating emotional symptoms such as anxiety, anger, and excessive sadness. The instrument used was a previously validated adolescent emotional problems scale. Data analysis using the paired sample t-test revealed a significant difference between pretest and posttest scores after the CBT intervention was administered. These findings indicate that the CBT approach is effective in reducing the intensity of emotional problems in adolescents. Therefore, CBT can serve as an alternative psychological intervention in school settings to help students develop more adaptive emotional regulation. Recommendations are directed toward school counselors and school authorities to integrate CBT techniques into guidance and counseling services.